Consumer Buying Behaviour towards Toothpaste - Acharya, S; Ubeja, S; Jain, P; Loya, A (International Journal of Computer Sciences and Engineering, 2025)
"Shopper is dealt with as the ruler of market", since items are made, outlined and permitted to come in showcase as per the need and inclinations of the customers. In this way, accomplishment of any association dependably relies upon having the capacity to pull in, fulfill and hold clients. This requires a comprehension of what factors influence shoppers' fulfillment with an item or benefit and what decides their choice to buy an item. In light of the different investigation of logical writing, brand is a key factor and it produces consumer loyalty. For pulling in and holding clients, branding is one of the critical variables which impact on buyer purchasing conduct. This paper analyses upon mindfulness and client ship of various toothpaste brand Buyers. It additionally centers around understanding the demographic factors of purchasers which eventually impacts on purchasing toothpaste. Other than that the study has directed by the researcher to discover different reasons which are impacted by factors of brand switching towards toothpaste.